First steps towards initial registration for electrophysiology procedures - Brost, Alexander; Bourier, Felix; Yatziv, Liron; Koch, Martin; Hornegger, Joachim; Strobel, Norbert; Kurzidim, Klaus (Medical Imaging 2011: Visualization, Image-Guided Procedures, and Modeling, 2011)
Atrial fibrillation is the most common heart arrhythmia and a leading cause of stroke. The treatment option of choice is radio-frequency catheter ablation, which is performed in electrophysiology labs using C-Arm X-ray systems for navigation and guidance. The goal is to electrically isolate the pulmonary vein-left atrial junction thereby rendering myocardial fibers responsible for induction and maintenance of AF inactive. The use of overlay images for fluoroscopic guidance may improve the quality of the ablation procedure, and can reduce procedure time. Overlay images, acquired using CT, MRI, or C-arm CT, can add soft-tissue information, otherwise not visible under X-ray. MRI can be used to image a wide variety of anatomical details without ionizing radiation. In this paper, we present a method to register a 3-D MRI volume to 2-D biplane X-ray images using the coronary sinus. Current approaches require registration of the overlay images to the fluoroscopic images to be performed after the trans-septal puncture, when contast agent can be administered. We present a new approach for registration to align overlay images before the trans-septal puncture. To this end, we manually extract the coronary sinus from pre-operative MRI and register it to a multi-electorde catheter placed in the coronary sinus. © 2011 SPIE.